Coherent interaction of light with a single molecule and a plasmonic nanoparticle - Zirkelbach, Johannes; Türschmann, Pierre; Renger, Jan; Utikal, Tobias; Götzinger, Stephan; Sandoghdar, Vahid (Optics InfoBase Conference Papers, 2019)
We demonstrate partial cloaking of a gold nanoparticle by a single organic molecule as a result of their coherent interaction with a monochromatic laser beam at cryogenic temperatures. Spectral and fluorescence lifetime analyses are presented.
CRIS-Team Scopus Importer:2019-07-09